Workload demands of laser class sailing regattas - Winchcombe, C.; Goods, P.; Binnie, M.; Doyle, M.; Fahey-Gilmore, J.; Peeling, P. (International Journal of Performance Analysis in Sport, 2021)
This study aimed to quantify the workload demands, internal stress response and perceptual fatigue experienced by Laser class sailors across multiple days of competition. Eleven elite male Laser Standard athletes (age: 23.2 ± 3.4y, body mass: 82.6 ± 2.3 kg, stature: 182 ± 5 cm) competing at two regattas were recruited. Athletes wore a heart rate (HR) monitor and global positioning system (GPS) unit whilst racing and completed a daily short recovery and stress scale (SRSS). Athletes spent longer sailing upwind (29:08 ± 2:13 min:s) than on a reach (5:19 ± 1:11 min:s), (P < 0.001) and downwind (13:13 ± 3:04 min:s), (P < .001) in each race. Mean HR during upwind sailing (159 ± 11 beats per minute (bpm)) was higher than downwind sailing (147 ± 15 bpm), (P < 0.001) and reaching (156 ± 16 bpm), (P = 0.002). Although regatta schedules are highly governed by environmental conditions, this study confirms that sailing upwind (i.e., hiking) is the most physically demanding aspect of racing. Additionally, perceptual fatigue increases over time in more demanding regatta schedules. These findings provide a framework to prescribe training and recovery regimes for Laser class sailing athletes, to optimise physical performance during sailing regattas.